Uso do índice tornozelo-braquial como preditor de eventos cardiovasculares em pacientes idosos portadores de doença arterial coronária - Papa, Eduardo Diodati Esposito [UNIFESP] (2017)
Objective: This populational study aims to correlate the ankle-brachial index with cardiovascular morbidity and mortality and with the extent of coronary disease in elderly outpatients, asymptomatic for peripheral arterial disease of lower limbs. Methods: We analyzed, prospectively, 100 patients aged 65 years or more, from geriatric cardiology clinic of the Universidade Federal de São Paulo, with coronary artery disease, documented by coronary angiography (stenosis greater than or equal to 50% of left main coronary artery/or stenosis greater than 70% in at least one sub-epicardial coronary artery ). Immediately after, we measured the ankle-brachial index and a value of less than 0.90 was used for diagnosis of peripheral artery disease. The evaluation of patients was obtained in two phases: initial ( average 28.9 months ) and the late follow-up (average 70.8 months), when the major cardiovascular events were evaluated by: cardiovascular and overall mortality; Acute myocardial infarction, fatal and non-fatal; and stroke, fatal or non-fatal Results: The patients average age at baseline was 77.4 years and at late follow –up was 82.9 years. We obtained the late follow-up (71,2 months) of all patients. We found a high prevalence of Hypertension (96%), being the acute myocardial infarction the predominant clinical manifestation and, at the time of inclusion, all were asymptomatic for peripheral artery disease, as well as on late evaluation. In 47%, the ankle-brachial index was less than 0.90 and it was more prevalent in those with multiarterial coronary disease when compared with patients with uniarterial disease of the same group (83% x 17%, respectively, p = 0.004). As a result, in the short- term follow – up the reduced ankle-brachial index was an important predictor of events, associated with overall mortality (relative risk 3.01, p = 0.070), acute myocardial infarction fatal and non-fatal (relative risk 2.54, p = 0.085) and major cardiovascular events (relative risk 2.70, p = 0.032), when adjusted to smoking, diabetes mellitus, gender (female) and extent of coronary disease (multiarterial disease). In the late follow-up, the reduced ankle-brachial index remained as a predictor of major cardiovascular events (relative risk 1.58, p = 0.029) and overall mortality (relative risk 1.48, p = 0.081), as well as Diabetes Mellitus (relative risk 1.56, p = 0.030 and 1.71, p = 0.016), respectively, when assessed in relation to smoking and gender (female). Adjusting for extension of coronary artery disease and Diabetes, the Reduced Ankle-Brachial Index was still associated with major cardiovascular events. Conclusion: In elderly outpatients with documented coronary artery disease and asymptomatic for peripheral arterial disease, the reduced ankle-brachial index was correlated with the extent of coronary artery disease and, in the initial follow-up, was associated with an increased risk of overall mortality and a higher incidence of acute myocardial infarction, fatal and nonfatal, in this population, increasing this risk by two to three fold. In the late follow-up, the reduced ankle-brachial index maintained this correlation, but to a lesser extent when compared to the initial follow-up, suggesting that the reduced brachial ankle index is a more significant marker of short-term major events in the studied population.